PERUBAHAN JUMLAH SEL PURKINJE SEREBELUM TIKUS WISTAR JANTAN SETELAH PEMAPARAN ROKOK ELEKTRIK - Rambung, Etha (E-Jurnal Medika Udayana; Vol 12 No 9 (2023): E-Jurnal Medika Udayana, 2023)
Design, taste, marketing and perceptions of safety from e-cigarettes have increased the appeal of e-cigarettes to young people around the world so that their use continues to increase. This is one of the threats in efforts to reduce the prevalence of smokers aged 10-18 years in Indonesia. Electric cigarettes cause oxidative stress while the brain is vulnerable to oxidative stress because it requires large amounts of oxygen. This experimental study with a posttest only control design aimed to determine changes in histological structure and number of male Wistar rat cerebellum Purkinje cells after exposure to electric cigarettes. This study used a sample of 32 male wistar rats (Rattus norvegicus) which were divided into 4 treatment groups:  group A (without treatment), group B (put in an exposure cage), group C (given exposure to electric cigarettes 15 times in a cage exposure), and group D (given exposure to e-cigarettes 30 times in the exposure cage). Exposure to e-cigarettes was given for 50 days, then sacrificed and samples were made with Hematoxylin Eosyn (HE) staining. The results showed that the number of cerebellar purkinje cells in male Wistar rats exposed to electric cigarettes decreased significantly and there was a significant difference in the number of cells between 15 and 30 exposures and karyolysis occurred in the cells. E-cigarettes cause core damage and decrease in the number of Purkinje cells in the cerebellum of male wistar rats.